The impact of exercising self-efficacy on physical education learning engagement: the mediating role of flow experience - Huang, Wenzhe; Wei, Ruikai; Cheng, Bojin (Frontiers in Psychology, 2025)
IntroductionThe study aims to examine the direct and indirect effects of exercising self-efficacy on physical education learning engagement through mediator flow experience.MethodsBased on a questionnaire survey, using the Exercise Self-efficacy Scale, Flow Experience Scale, and Physical Education Learning Engagement Scale, a survey was conducted among 568 university students from five universities in Guangdong Province, China.Results① There were significant positive correlations between exercise self-efficacy, flow experience, and physical education learning engagement; ② Exercise self-efficacy positively influenced physical education learning engagement; ③ Flow experience played a mediating role between exercise self-efficacy and physical education learning engagement.DiscussionThis study fills the theoretical gap of flow experience application in the context of physical education, and uses the variable of exercise self-efficacy, which combines individual self-efficacy with the field of physical exercise, to enhance the depth and strength of explanation and prediction. The findings of this study contribute to physical education instructors’ understanding of the psychological mechanisms at play in college students’ physical education learning process. Additionally, the examination of the pivotal mediating role of flow experience offers fresh perspectives for enhancing the efficacy of physical education instruction.